Peran Radio Komunitas dalam Menumbuhkembangkan Civic Community - ROCHMAD EFFENDY (Komunikator, 2012)
Community radio is basically unique media of communication which is viewed from how it was established, its operational management and its programs which are to build the society around it. Community radio is participatory media. It means community radio provides public sphere through horizontal communication among its members. Thus, it is seen as fertile ground for developing civic community whose members have an interest in discussing common problems in the same position that binds them together through collective association in civic values. It shows that in the beginning, the operational management followed the basic rules and the ideal principles. Unfortunately, the management of Mustika is more like daily broadcasting principles which are similar to private radios. Keywords: Community Radio, Radio Management, Participatory Media